Efficient, yet insufficient: Investigating Transit-Oriented Policies at the national level - Abdi, Mohammad; Mirmoghtadaee, Mahta (Spatium, 2025)
The initial design concept of Transit-Oriented Development (TOD) has emerged as a key urban policy to address urbanization challenges worldwide, drawing on an integrated transportation and land use planning approach. Although TOD policies are typically formulated at the local level, addressing related subjects such as parking and zoning codes, some governance systems elevate them to the national level to guide lower-tier policies. For instance, in Iran ? a newcomer to TOD ? a national TOD policy has recently been introduced as part of a TOD policy package. However, there remains uncertainty about the extent to which a national guideline can contribute to successful TOD implementation, support local tiers, and ensure the achievement of TOD goals. The present research aims to address this gap by shedding light on the Iranian experience through a qualitative approach. The findings indicate that a National Transit-Oriented Development Guideline (NTODG) is among the ?efficient? instruments available to governments for advancing TOD culture ? particularly in developing-country cities as newcomers to TOD, where the integration of transport and land use faces numerous challenges. However, NTODGs tend to be ?insufficient? on their own, as they must be coordinated with other related policies under a ?stable? political system and planning framework to turn TOD aspirations into reality.